Seleksi Peserta Didik Baru Menggunakan Metode AHP Dan SAW - Lestari, Yuniarti; S, Sunardi; Fadlil, Abdul (STIKOM Tunas Bangsa Pematangsiantar, 2020)
The admission activity of new students is an administrative process that is sure to occur every new school year and always repeats every year as a starting point for the search for quality resources in accordance with the criteria of each school. Selection is done manually such as using a spreadsheet or number processor still raises several problems including the length of the selection process. At the time of the participant selection process, it involved many criteria that were assessed (multi criteria). Efforts to assist the school in selecting participants from the results considered to be acceptable results require a decision support system for selecting new students. The method used to support students' selection decisions is AHP and SAW. AHP method is used to determine the weight of predetermined criteria, while the SAW method is used for alternative ranking. The purpose of alternative ranking is who has the right to be accepted as a new student based on predetermined criteria.